The crisis governance of the European Union: More responsibility requires more democratic legitimacy - Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2023)
Since 2010, amid a series of overlapping crises, the EU has introduced far-reaching instruments both within and beyond the EU treaties that have expanded its responsibilities. These instruments often have a structure-defining character and/or have served as precedents in subsequent crises. An analysis of the decision-making processes on three key crisis instruments during the Covid-19 pandemic - vaccine procurement, the SURE programme to support national short-time working schemes and the recovery fund NGEU - reveals deficits in the democratic legitimacy of the EU's crisis governance. The "emergency Article" 122 TFEU, which was used for all three crisis instruments, largely excludes the involvement of the European Parliament. As NGEU was linked to the EU's Multiannual Financial Framework, the EP was involved but politically marginalised by the member states in the Council. Because standard EU procedures were used, the German Bundestag was informed in all three cases and was even able to secure more extensive information rights than the EP. However, this cannot replace European-level parliamentary control. As far as the capacity to act in decision-making processes is concerned, Article 122 TFEU with majority voting allowed for very quick decisions to be made regarding vaccine procurement and SURE, but not NGEU. The model of NGEU - with a link to the Multiannual Financial Framework and lengthy national approval procedures - is therefore not suitable as a model for crisis instruments. There are clear deficiencies in the transparency of decision-making processes and implementation as well the allocation of political responsibility. In the short term, the EU should increase the transparency of crisis instruments; in the long term, it should introduce a clear definition of a "state of emergency", with appropriate limits, into the EU Treaty, while strengthening the role of the EP.
Keywords: 320; Krisengovernance; Kriseninstrumente; Bewältigung von Covid-19; Bewältigung der Pandemie; Mehrebenensystem; nationale und EU-Ebene; EU-Institutionen; EU-Kommission; Rat der EU; Europäischer Rat; Entscheidungsprozesse in der EU; Entscheidungsverfahren in der EU; Gesetzgebung in der EU; Handlungsfähigkeit der EU; Einstimmigkeit; qualifizierte Mehrheit; politische Verantwortung; Transparenz; demokratische Legitimation; Artikel 122 AEUV; Notstandsklausel; Impfstoffbeschaffung; Kurzarbeitergeld-Programme; SURE; europäische Arbeitslosenversicherung; NGEU; Next Generation EU; Wiederaufbaufonds; Bundesregierung; Bundestag